Mengukur Kesiapan Etika Digital Dalam Analisis Persepsi Multidisiplin Mahasiswa Universitas Negeri Medan Terhadap Pancasila Sebagai Dasar Nilai Pengembangan Ilmu (DPI) Dalam Menghadapi Disrupsi Teknologi - Manalu, Syuratty Astuti Rahayu; Nainggolan, Yesi Rama Indah; Nasution, Nur Hidayati; Pandiangan, Betrand Samuel; Tarigan, Peter Teguh; Silalahi, Ritayana; Sarumaha, Elisabeth S. Putri (Yayasan Sagita Akademia Maju, 2025)
This study aims to measure the readiness and analyze the perceptions of Universitas Negeri Medan (UNIMED) students across various faculties regarding the implementation of Pancasila as the Basis for scientific development values (DPI) within digital ethics practices. The core problem addressed is the gap between the ideological recognition of Pancasila and the reality of behavior in cyberspace, which is susceptible to technological disruption and moral crises. A descriptive qualitative method, utilizing in-depth interviews across different faculties at UNIMED, was employed to identify the convergence and conflict of values in technology use. The research results consistently indicate that students acknowledge the urgency of Pancasila as a